Neotype designation of Aphanius iconii, first reviser action to stabilise the usage of A. fontinalis and A. meridionalis and comments on the family group names of fishes placed in Cyprinodontidae (Teleostei: Cyprinodontiformes) - Freyhof, Jörg; Özuluğ, Müfi̇t; Saç, Gülşah (Zootaxa, 2017)
As First Revisers, we give priority to Aphanius fontinalis over A. altus and A. litoralis and to A. meridionalis over A. parvus. A neotype is designated from Lake Eğirdir for Aphanius iconii. Family groups in the deeply polyphyletic fish family Cyprinodontidae are discussed. Aphaniidae, Cubanichthyidae and Orestiidae are proposed as distinct families, restricting the family Cyprinodontidae to the New World genera Cualac, Cyprinodon, Floridichthys, Jordanella and Megupsilon.